The intersectional effects of motivational and affective factors on managers’ performance - Junça Silva, A.; Mendes, S. (Applied Psychology - Health and Well-Being, 2023)
Purpose: Drawing from the effort-recovery model, the authors analysed the role of daily sleep quality as a driver for self-regulatory resources and consequently of task and contextual performance. Specifically, the authors hypothesised that self-regulatory resources would be a potential mechanism for enhancing workers’ performance after a good night's sleep. Moreover, relying on the COR theory, the authors proposed health-related indicators (mental health and vitality) as intensifiers of the previously proposed indirect effect. Design/methodology/approach: Daily diary data were collected from 97 managers over five consecutive working days (485 daily observations) and analysed using multilevel analyses. Findings: Sleep quality was positively associated with managers’ self-regulatory resources and (task and contextual) performance at the person and day levels. Additionally, results provided support for most of the assumed indirect effects of sleep quality on both performance dimensions via self-regulatory resources. At last, the findings evidenced that these indirect effects were moderated by health indicators in a way that lower scores on health intensified such positive effects. Practical implications: Organisations should create mechanisms that could promote their workers’ awareness of the potential benefits of sleeping well at night as well as its impacts on both self-regulatory resources and performance. The current intensification of workload together with working after hours may pose a risk to this important resource source for managers. Originality/value: These findings emphasise the day-to-day variation in self-regulatory resources needed to perform and that workers’ sleep quality has the potential to stimulate a resource-building process for such benefits.